2021
DOI: 10.2478/jeb-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Real Effective Exchange Rate and Industrial Productivity in Croatia: Wavelet Coherence Analysis

Abstract: This paper brings releationship between real effective exchange rate and industry production in Croatia. Research sample consists of monthly data from January 2000 up to June 2019. Following wavelet coherence approach, empirical results reveal the relationship across time and frequency domain. The empirical obtained from wavelet coherence analysis and confirmed with conventional correlation analysis suggested positive relationship between industrial productivity and real effective exchange rate in Croatia, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…This can lead to a decline in export demand, resulting in potential job losses in sectors reliant on export markets (Bošnjak, 2021). Conversely, when the REER depreciates, exports become more competitive internationally, leading to increased demand for domestically produced goods and supporting employment in export-oriented industries (Bošnjak et al, 2021). Empirical studies provide evidence of a significant relationship between changes in the REER and employment fluctuations in countries such as China and Mexico, highlighting the importance of exchange rate movements in shaping labor market outcomes (Hegeland & Taalbi, 2019).…”
Section: Fluctuations In the Real Effective Exchange Rate And Unemplo...mentioning
confidence: 99%
“…This can lead to a decline in export demand, resulting in potential job losses in sectors reliant on export markets (Bošnjak, 2021). Conversely, when the REER depreciates, exports become more competitive internationally, leading to increased demand for domestically produced goods and supporting employment in export-oriented industries (Bošnjak et al, 2021). Empirical studies provide evidence of a significant relationship between changes in the REER and employment fluctuations in countries such as China and Mexico, highlighting the importance of exchange rate movements in shaping labor market outcomes (Hegeland & Taalbi, 2019).…”
Section: Fluctuations In the Real Effective Exchange Rate And Unemplo...mentioning
confidence: 99%
“…In Malaysia, Sadia,et al [4] found the lending rate and inflation were considerable determinants of the volatility in reer in the short-term while in the long-term, GDP deflator, total export/GDP ratio, and domestic inflation rate were the significant drivers of volatility in the reer. In Croatia, Bošnjak, et al [5] found significant connection between reer and industrial productivity basing estimation on the Wavelet Coherence method. The study by Ogundipe & Lawal (2014) employs an econometric approach to analyze the relationship between the reer and various macroeconomic variables.…”
Section: Survey Of Relevant Literaturementioning
confidence: 99%
“…Štoviše, glavna prepreka jačanju hrvatskog regionalnog izvoza je nedostatak domaće potražnje i smanjenje produktivnosti rada (Stojčić, Bečić & Vojinić, 2012;Jakšić, Erjavec & Cota, 2019), dok su geografska udaljenost glavnih gradova i broj stanovnika starijih od 15 godina u zemlji partnerici (tj. veličina tržišta) glavne odrednice robnog izvoza (Bošnjak, Novak i Bašić, 2022), dok je realni efektivni devizni tečaj, odnosno deprecijacija realnog deviznog tečaja, pozitivno povezana s produktivnošću industrije (Bošnjak, Kordić & Novak, 2021), a što se posebice odnosi na turizam (Bošnjak, Bilas & Franc, 2018). Finalno, Stojčić i Vojinić (2022) ispitivali su posljedice diverzifikacije i koncentracije izvoza na ulazak, opstanak i rast poduzeća na tržištu tehnikama prostorne ekonometrije na financijskim podacima poduzeća.…”
Section: Pregled Literatureunclassified